2015
DOI: 10.4161/15384101.2014.989126
|View full text |Cite
|
Sign up to set email alerts
|

The Slx4-Dpb11 scaffold complex: coordinating the response to replication fork stalling in S-phase and the subsequent mitosis

Abstract: Replication fork stalling at DNA lesions is a common problem during the process of DNA replication. One way to allow the bypass of these lesions is via specific recombination-based mechanisms that involve switching of the replication template to the sister chromatid. Inherent to these mechanisms is the formation of DNA joint molecules (JMs) between sister chromatids. Such JMs need to be disentangled before chromatid separation in mitosis and the activity of JM resolution enzymes, which is under stringent cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…We also noted that the phenotype of this MMS4 variant differed from that induced by Dpb11 binding‐deficient version of Slx4 [ slx4‐S486A (Gritenaite et al , ; Ohouo et al , )]. This could suggest that these mutants are able to separate different Dpb11 functions such as a mitotic function in conjunction with Mus81‐Mms4 and an S‐phase function, which Slx4 and Dpb11 might have independently of Mus81‐Mms4 (Ohouo et al , ; Gritenaite et al , ; Cussiol et al , ; Princz et al , ). However, it also needs to be considered that Slx4 and Mus81‐Mms4 may be connected by more than one scaffold protein (see below).…”
Section: Resultsmentioning
confidence: 93%
“…We also noted that the phenotype of this MMS4 variant differed from that induced by Dpb11 binding‐deficient version of Slx4 [ slx4‐S486A (Gritenaite et al , ; Ohouo et al , )]. This could suggest that these mutants are able to separate different Dpb11 functions such as a mitotic function in conjunction with Mus81‐Mms4 and an S‐phase function, which Slx4 and Dpb11 might have independently of Mus81‐Mms4 (Ohouo et al , ; Gritenaite et al , ; Cussiol et al , ; Princz et al , ). However, it also needs to be considered that Slx4 and Mus81‐Mms4 may be connected by more than one scaffold protein (see below).…”
Section: Resultsmentioning
confidence: 93%
“…Our previous work also showed that concomitant with the activation in M phase, Mus81‐Mms4 also engages in interactions with several scaffold proteins: Dpb11, Rtt107 and Slx4 (Fig. ).…”
Section: Mus81 Regulation In S Cerevisiae: Activation At the G2/m Trmentioning
confidence: 70%
“…According to the most recent data, we will specifically focus on Mus81 control in budding yeast and human cells, even though analogous principles of control are found in fission yeast and are likely to be present in other organisms. While previous reviews covered complementary aspects of Mus81 regulation , we will, given the highly dynamic nature of this topic and the recent discovery of important new players in the regulation of Mus81, provide an updated model. The following reviews provide excellent insights into the discovery and biochemical properties of Mus81 in different systems .…”
mentioning
confidence: 99%
“…It involves the invasion of nascent DNA on the sister strand, which is used as a template to bypass a potential obstacle on the template strand (reviewed in ref. 43 ). Translesion synthesis (TLS) applies socalled translesion polymerases to restart the fork (reviewed in ref.…”
Section: Topbp1 Is Required For Atr Activationmentioning
confidence: 99%